Penyebaran Hoax: Perspektif Islam Dan Hadis Tentang Kebohongan Dalam Berita - Sitta Khairunnisa; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to discuss the spread of hoaxes from an Islamic perspective, focusing on the teachings of Hadith. The methodology involves a qualitative approach through the study of religious texts, specifically Hadith, to understand the moral implications of hoaxes. The study also explores the significance of raising public awareness about hoaxes and their potential consequences on society. The findings suggest that hoaxes are considered a form of deception and are strongly discouraged in Islamic teachings. The study concludes by emphasizing the importance of adhering to Islamic communication ethics in dealing with hoaxes, such as verifying information before sharing it and being cautious about the impact of one's words.